Degradation of a Foreland River After the Wenchuan Earthquake, China: A Combined Effect of Weirs, Sediment Supply, and Sediment Mining - Yongpeng Lin; Chenge An; Shan Zheng; Ruihua Nie; Gary Parker; Marwan A. Hassan; Matthew J. Czapiga; Xudong Fu (Water Resources Research)
Abstract Since the 2008 Wenchuan (Ms. 8.0) Earthquake, the foreland rivers of the Longmen Mountains have suffered from significant bed degradation, among which the Shi‐ting River has experienced the largest local degradation of more than 20 m in 7 years. Potential reasons of the dramatic degradation include: (a) sediment disconnectivity due to in‐channel weirs; (b) the mobilization effect on gravel of an increased sand supply as a result of earthquake‐induced landslides; and (c) sediment extraction due to intensive mining. In this paper, we study the complex interaction among the above‐mentioned factors in the Shi‐ting River, using a one‐dimensional river morphodynamic model. Simulation results show that in‐channel weirs can reduce bedload transport and lead to bed degradation that is proportional to weir height. When coupled with additional sand supply, the weirs preferentially trap gravel and deliver sand, augmenting the downstream mobility of gravel and thus the degradation. For the Shi‐ting River, the simulated bed degradation agrees well with the observation when an annual sediment mining of 16 million tons is implemented in the simulation, along with the effects of in‐channel weirs and sand supply. The contribution of sediment mining is one order of magnitude larger than the coupling effect of weirs and sand supply. Both the simulation and observation show that the largest bed degradation occurs downstream of the Renmin Weir, due to the large spatial interval between the Renmin Weir and the next grade control structure.